Analysis of biomass productivity and physiology of Nitrososphaera viennensis grown in continuous culture - Melcher, Michael; Hodgskiss, Logan H.; Mardini, Mohammad Anas; Schleper, Christa; Rittmann, Simon K.-M. R. (Frontiers in Microbiology, 2023)
Microbial ammonia oxidation is the first and usually rate limiting step in nitrification and is therefore an important step in the global nitrogen cycle. Ammonia-oxidizing archaea (AOA) play an important role in nitrification. Here, we report a comprehensive analysis of biomass productivity and the physiological response of Nitrososphaera viennensis to different ammonium and carbon dioxide (CO2) concentrations aiming to understand the interplay between ammonia oxidation and CO2 fixation of N. viennensis. The experiments were performed in closed batch in serum bottles as well as in batch, fed-batch, and continuous culture in bioreactors. A reduced specific growth rate (μ) of N. viennensis was observed in batch systems in bioreactors. By increasing CO2 gassing μ could be increased to rates comparable to that of closed batch systems. Furthermore, at a high dilution rate (D) in continuous culture (≥ 0.7 of μmax) the biomass to ammonium yield (Y(X/NH3)) increased up to 81.7% compared to batch cultures. In continuous culture, biofilm formation at higher D prevented the determination of Dcrit. Due to changes in Y(X/NH3) and due to biofilm, nitrite concentration becomes an unreliable proxy for the cell number in continuous cultures at D towards μmax. Furthermore, the obscure nature of the archaeal ammonia oxidation prevents an interpretation in the context of Monod kinetics and thus the determination of KS. Our findings indicate that the physiological response of N. viennensis might be regulated with different enzymatic make-ups, according to the ammonium catalysis rate. We reveal novel insights into the physiology of N. viennensis that are important for biomass production and the biomass yield of AOA. Moreover, our study has implications to the field of archaea biology and microbial ecology by showing that bioprocess technology and quantitative analysis can be applied to decipher environmental factors affecting the physiology and productivity of AOA.